2014
DOI: 10.1152/jn.00522.2014
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic transmission between end bulbs of Held and bushy cells in the cochlear nucleus of mice with a mutation in Otoferlin

Abstract: Wright S, Hwang Y, Oertel D. Synaptic transmission between end bulbs of Held and bushy cells in the cochlear nucleus of mice with a mutation in Otoferlin. J Neurophysiol 112: 3173-3188, 2014. First published September 24, 2014 doi:10.1152/jn.00522.2014.-Mice that carry a mutation in a calcium binding domain of Otoferlin, the putative calcium sensor at hair cell synapses, have normal distortion product otoacoustic emissions (DPOAEs), but auditory brain stem responses (ABRs) are absent. In mutant mice mechanotr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 98 publications
(89 reference statements)
3
25
1
Order By: Relevance
“…This suggests that otoferlin may play a developmental role and that the lack of otoferlin during a certain developmental window may have permanent effects on zebrafish physiology. In support of this, a recent study reported abnormally small ventral cochlear nuclei in otoferlin knockout mice (56). Future studies should focus on the developmental effects linked to otoferlin loss of function.…”
Section: Discussionmentioning
confidence: 63%
“…This suggests that otoferlin may play a developmental role and that the lack of otoferlin during a certain developmental window may have permanent effects on zebrafish physiology. In support of this, a recent study reported abnormally small ventral cochlear nuclei in otoferlin knockout mice (56). Future studies should focus on the developmental effects linked to otoferlin loss of function.…”
Section: Discussionmentioning
confidence: 63%
“…), similar to the observation in the AVCN of Otof KOs (Wright et al . ). In contrast, eEPSCs at the calyx–MNTB synapse are normal in dn/dn mice (Oleskevich et al .…”
Section: Discussionmentioning
confidence: 97%
“…; Wright et al . ). The non‐functionality of otoferlin is due to a missense point mutation in the gene part encoding the C2B domain, one of six C2 domains in the 230 kDa protein.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…; Wright et al . ). During this critical period, the activity of endbulb of Held‐BC synapse can be enhanced by ATP (Dietz et al .…”
Section: Discussionmentioning
confidence: 97%